Evaluation of serum antibody responses of Madras Red sheep to excretory/secretory antigen of Haemonchus contortus - Arunkumar, S; Basith, S Abdul; Gomathinagayam, Gomathinagayam (The Indian Journal of Animal Sciences, 2012)
Excretory/secretory (E/S) antigen from Haemonchus contortus was isolated by culturing live adult worms in RPMI 1640 medium at 37° C for 24 h and the culture supernatant was used as antigen. Immuno blot analysis revealed that the E/S antigen showed 5 reactive bands at 24, 29, 46, 66 and 93 kDa. On immunization trial, sheep were immunized with 500 mg of E/S antigen along with montanide as adjuvant on day 0, 30 and 60 intramuscularly. Further, the assessment of serum antibody levels in immunized sheep was made by enzyme linked immuno sorbent assay (ELISA). Based on absorbance values, it was observed that the serum antibody levels were significantly higher up to 20 weeks post immunization in immunized sheep compared to control sheep.